OPTN/SRTR 2018 Annual Data Report: Kidney - Allyson Hart; Jodi M. Smith; M.A. Skeans; S.K. Gustafson; Amber R. Wilk; Sara Sánchez Castro; J. Foutz; Jennifer L. Wainright; Jon J. Snyder; Bertram L. Kasiske; Ajay K. Israni (2020)
Despite the ongoing severe mismatch between organ need and supply, data from 2018 revealed some promising trends. For the fourth year in a row, the number of patients waiting for a kidney transplant in the US declined and numbers of both deceased and living donor kidney transplants increased. These encouraging trends are tempered by ongoing challenges, such as a large proportion of listed patients with dialysis time longer than 5 years. The proportion of candidates aged 65 years or older continued to rise, and the proportion undergoing transplant within 5 years of listing continued to vary dramatically nationwide, from 10% to nearly 80% across donation service areas. Increasing trends in the recovery of organs from hepatitis C positive donors and donors with anoxic brain injury warrant ongoing monitoring, as does the ongoing discard of nearly 20% of recovered organs. While the number of living donor transplants increased, racial disparities persisted in the proportion of living versus deceased donors. Strikingly, the total number of kidney transplant recipients alive with a functioning graft is on track to pass 250,000 in the next 1-2 years. The total number of pediatric kidney transplants remained steady at 756 in 2018. Deeply concerning to the pediatric community is the persistently low level of living donor kidney transplants, representing only 36.2% in 2018.